Capital Structure and Their Influence on Firm Value in Indonesia’s Consumer Cyclicals Sector - Anggraeni, Dhea Puspita; Rohmawati Kusumaningtias; Muthohhari, Abdullah Hanif (Muhasabatuna : Jurnal Akuntansi Syariah, 2025)
This study aims to analyze the effect of capital structure on the firm value of consumer cyclicals sector companies in Indonesia for 2018-2023. Capital structure is measured using Debt to Equity Ratio (DER), Debt to Asset Ratio (DAR), Long-term Debt to Equity Ratio (LDER), and Long-term Debt to Asset Ratio (LDAR), while firm value is measured by Tobin's Q. The results showed that DER has a significant negative effect on firm value, where an increase in DER reduces Tobin's Q due to high debt that exceeds the optimal limit. In contrast, LDER has a significant positive effect, reflecting the success of long-term debt management to support firm value. However, DAR and LDAR have no significant effect, indicating that investors pay less attention to asset financing through debt. This study supports the trade-off theory that explains the optimal relationship between the use of debt and firm value. The research results are expected to be a reference for companies in managing capital structure to increase their firm value